Online public access catalogue [OPAC] in Nigerian libraries: a case study of the Kenneth Dike Library and university of lagos library (2013)
This research work examined the effects and constraints of Online Public Access Catalogue (OPAC) in Nigerian Libraries: A case study of. Kenneth Dike Library and University of Lagos Library. The research design is a case study and data was gathered from randomly selected students over a period of one week. Out of a total of 200 questionnaires used,a total of 190-were returned out of which 164 were found useful. Frequency counts and simple percentage were used to analyze the data. The findings of the study showed that the major effects of OPAC is that it allows users to search the library's collection from location outside the library walls: it provides users with timely access to library materials: it encourages cooperative collections development and resource sharing and power failure was also indicated as one of the numerous problems facing the utilization of OPAC in Nigeria Libraries. From the findings of the study, conclusions and recommendations were made.